Case series: Four fatal rabbit hemorrhagic disease virus infections in urban pet rabbits - Pinto, Filipe Fontes; Abrantes, Joana; Ferreira, Paula Gomes; Nóbrega, Mário; Marcos, Ricardo (Frontiers in Veterinary Science, 2023)
Four pet rabbits (Oryctolagus cuniculus cuniculus) diagnosed with a fatal infection by rabbit hemorrhagic disease virus (RHDV GI.2) were identified in the same week and further investigated. All animals lived in an urban environment (Lisbon, Portugal), were between 8 months and 2 years old and none had been vaccinated against RHDV2 (GI.2). Three animals arrived at the clinic and died shortly afterward and it was only possible to collect material for RT-qPCR (RHDV) test. These rabbits tested positive for RHDV2, with high viral loads. In the fourth case, additional clinical and post-mortem gross and histological evaluations were performed. This 8 month old intact female indoor pet rabbit was presented with apathy, tachypnea and tachycardia. Radiographic projections revealed no clinical revealed no clinical abnormalities. Serum biochemistry revealed a significant increase in AST and ALT with a small hypoglycemia. Abdominal ultrasound revealed an acute hepatitis. Despite hospitalization support, after 30 h of admission, the rabbit lost consciousness and developed anorexia and pyrexia in the last minutes before death. Post-mortem analysis and molecular testing by RT-qPCR, confirmed the diagnosis of RHDV2 (GI.2) infection also with high viral load. In conclusion, this paper reports a case series that demonstrates the severe infectious ability and the high mortality associated with RHDV even in rabbits from urban environments. Furthermore, it highlights the importance of always considering rabbit hemorrhagic disease (RHD) as a differential diagnosis in pet rabbits with non-specific clinical signs, and should warn veterinarians that pet rabbits living indoors can also be infected with a fatal outcome.